Occurence and fate of pharmaceuticals and personal care products in wastewater environment - Mission, Elaine G. (Animo Repository, 2008)
Pharmaceuticals and personal care products PPCPs) are chemical preparations which aim to treat or prevent ailments. With huge volume of these substances being produced, marketed and utilized each day worldwide, its existence, fate and transport has been evident in the wastewater environment. Analgesics such as ibuprofen and antibiotics such as erythromycin detected in wastewater pose subtle, persistent and cumulative effects to aquatic organisms and may increase drug-resistance of microorganisms. Chemical coagulation treats finely dispersed particles and produces larger aggregates which can be separated physically. This multi-stage system that needs large area and continuous supply of dosing chemicals tends to produce large volume of sludge with high bound water content that can be difficult to dewater. A more compact treatment system which uses minimal additives and which produces flocs with less bound water and can replace chemical coagulation is electrocoagulation. This paper presents a review of literature on the application of electrocoagulation as treatment of pharmaceuticals and personal care products.